2023
DOI: 10.3390/ijms24098001
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max L.) Lipoxygenase 1 (LOX 1) Is Modulated by Nitric Oxide and Hydrogen Sulfide: An In Vitro Approach

Abstract: Hydrogen sulfide (H2S) and nitric oxide (NO) are two relevant signal molecules that can affect protein function throughout post-translational modifications (PTMs) such as persulfidation, S-nitrosation, metal-nitrosylation, and nitration. Lipoxygenases (LOXs) are a group of non-heme iron enzymes involved in a wide range of plant physiological functions including seed germination, plant growth and development, and fruit ripening and senescence. Likewise, LOXs are also involved in the mechanisms of response to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In many cases, these molecules act via modulating the metabolism of reactive oxygen species (ROS) both in antioxidant systems and in ROSgenerating enzymes [2,27,41,42]. Regulation is usually performed through posttranslational modifications (PTMs) such as nitration, S-nitrosation, and persulfidation [28][29][30][31]43]. The best-known examples are the antioxidant enzymes that scavenge H 2 O 2, such as catalase and ascorbate peroxidase (APX).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, these molecules act via modulating the metabolism of reactive oxygen species (ROS) both in antioxidant systems and in ROSgenerating enzymes [2,27,41,42]. Regulation is usually performed through posttranslational modifications (PTMs) such as nitration, S-nitrosation, and persulfidation [28][29][30][31]43]. The best-known examples are the antioxidant enzymes that scavenge H 2 O 2, such as catalase and ascorbate peroxidase (APX).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been seen that both NO and H 2 S can regulate protein function through post-translational modifications such as nitration, S-nitrosation, and persulfidation. Thus, some enzymes such as catalase, lipoxygenase, NADP-dependent dehydrogenase, NADP malic enzyme, or peroxidase undergo modifications via both molecules affecting their functions either positively or negatively [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a group of enzymes whose activity has been observed to be downregulated by H 2 S, including glutamine synthetase (GS) [ 32 ] and 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) in tomato [ 84 ], cysteine protease ATG4 [ 85 ], ATG18a [ 33 ], NADP-isocitrate dehydrogenase (NADP-ICDH) [ 86 ], NADP-malic enzyme (NADP-ME) [ 87 ], glucose-6-phosphate dehydrogenase (G6PDH) [ 29 ], catalase [ 88 ], flowering locus C protein (FLC1 and 3) [ 89 ], peroxidase IV [ 27 ], and lipoxygenase 1 (LOX 1) [ 90 ]. More recently, it has been shown that the persulfidation of cytosolic glucose 6-phosphate dehydrogenase in Arabidopsis and tomato can alter their homotetrameric structure and consequently the stability of the enzyme [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are also prevalent in the animal and plant kingdoms and play essential roles in resisting both biotic and abiotic stresses (Song et al, 2016). The biosynthesis of Lipoxygenases has been extensively studied in various plant species, including Arabidopsis thaliana (Melan et al, 1994), Triticum aestivum (Feng et al, 2012), Glycine max (González-Gordo et al, 2023), Arachis hypogaea (Mou et al, 2022) and Malus × domestica (Vogt et al, 2013). According to NCBI platform, 9 full length genes were recorded for Lipoxygenases (LOXs): 3 gene in Arabidopsis thaliana, 3 gene in Homo sapiens, 3 gene in Rattus norvegicus and one gene in Triticum aestivum .…”
Section: Introductionmentioning
confidence: 99%